Penning-trap measurement of the Q value of electron capture in 163Ho for the determination of the electron neutrino mass - Schweiger, Christoph; Braß, Martin; Debierre, Vincent; Door, Menno; Dorrer, Holger; Düllmann, Christoph E.; Enss, Christian; Filianin, Pavel; Gastaldo, Loredana; Harman, Zoltán; Haverkort, Maurits W.; Herkenhoff, Jost; et al. (Nature physics, 2024)
The investigation of the absolute scale of the effective neutrino mass remains challenging due to the exclusively weak interaction of neutrinos with all known particles in the standard model of particle physics. At present, the most precise and least-model-dependent upper limit on the electron antineutrino mass is set by the Karlsruhe Tritium Neutrino Experiment (KATRIN) from the analysis of the tritium β-decay. Another promising approach is the electron capture in 163Ho, which is under investigation using microcalorimetry by the Electron Capture in Holmium (ECHo) and HOLMES collaborations. An independently measured Q value for this process is vital for the assessment of systematic uncertainties in the neutrino mass determination. Here we report a direct, independent determination of this Q value by measuring the free-space cyclotron frequency ratio of highly charged ions of 163Ho and 163Dy in the Penning-trap experiment PENTATRAP. Combining this ratio with atomic physics calculations of the electronic binding energies yields a Q value of 2,863.2 ± 0.6 eV c−2, which represents a more than 50-fold improvement over the state of the art. This will enable the determination of the electron neutrino mass on a sub-electronvolt level from the analysis of the electron capture in 163Ho.
Online veröffentlicht: 19. April 2024
Die 163 im Titel ist hochgestellt
Gesehen am 30.10.2024